Pengharapan Akan Kedatangan Tuhan Yesus Yang Kedua Kali - Hendrik Irwansyah Zebua; Aprianus Ledrik Moimau, M.Th (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
An important part of eschatological teachings is futurist fact, which is the disclosure of future events through prophecies of the past. Therefore, Bible prophecy is at the center of the study and discussion of eschatological teachings. Eschatology is the most important doctrine that should be taught in the church, family and school environment as material for Christian religious education. The teaching of eschatology is very important to teach to students at school, so that they understand it and think about it. repent and believe in Jesus Christ and obtain the salvation of eternal life, now while you are still alive in the world and later when Jesus comes a second time to receive every believer. By knowing eschatology, students can prepare themselves spiritually with a firm belief that Jesus will come a second time to gather believers from the dead in the first stage of the resurrection, and people who are still alive at that time will experience the rapture. to heaven). In Christian religious education in schools, students must be taught that in the first stage of the resurrection, both Old Testament and New Testament believers, as well as believers who were still alive at the time of death, will experience resurrection. ; resurrected from the grave rapture), they become a glorified body like the Lamb of God. Christian religious formation must include advice to be alert, encouragement to work faithfully, development of skills, strengthening responsibility for all actions, and a glorious hope for the day of the Lord's return.